HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN RESILIENSI SISWA SERTA IMPLIKASI TERHADAP BIMBINGAN PRIBADI-SOSIAL - Isfaiyah Isfaiyah; Rahmawati Rahmawati; Raudah Zaimah Dalimunthe (Universitas Sultan Ageng Tirtayasa, 2019)
The objective of the study was to determine the relationship between peer social support and resilience. Quantitative method, especially correlational Study was employed in this study. The populations in this study were the students of SMA 2 Daar El Qolam Academic Year 2018/2019, and the samples were the students of class X Extention which amounted to 45 people. The classes were chosen by purposive sampling. In collecting the data, the researcher uses a measuring scale of peer social support 43 items with a reliability value of 0.914 and a measuring scale of resilience of 42 items with a reliability value of 0.869. In analyzing the data, the researcher used product moment analysis techniques. The results showed empirical data regarding the relationship of peer social support with resilience: (1) in general students of class X Extention SMA 2 Daar El Qolam had peer social support in a high category. (2) in general students of class X Extention SMA 2 Daar El Qolam have resilience in the medium category. And (3) the relationship of peer social support based on the results of statistical analysis obtained rxy value of 0.344 with a significance level of 0.021 (p <0.05). Therefore, it can be concluded that there was a significant positive relationship between peer social support and the resilience of students in class X Extention in Daar El Qolam 2 High School. Peer social support made an effective contribution of 11.8% to resilience.Keywords: Peer social support, Resilience